Błąd co do przymiotu osoby zamierzonego bezpośrednio i zasadniczo (kan. 1097 § 2 KPK) w świetle wyroku Roty Rzymskiej c. Bottone z 31 stycznia 2008 r. - Góralski, Wojciech (Ius Matrimoniale, 2016)
The case concerns marriage between Ad. and Adal., concluded in 1991. The woman decided to conclude marriage and wanted to conclude it according the law of Church and wanted her usband to have qualities thanks to which married life would be a true communion of life by mutual and joint actions. Before marriage she became convinced that her fiancé had all those qualities. However, almost immediately after the marriage was concluded, the man’s behaviour radically changed and their life together got worse and worse, so finally she left her husband. Then she brought the matter before the Tribunal of First Instance (canon 1097 § of Code of Canon Law), where a positive judgment was passed. Nevertheless, the judgment was negative in the Tribunal of Second Instance. As a result, the matter was brought before the Tribunal of Third Instance where again a positive judgement was passed, namely a judgment annulling the marriage (1.01.2008). The author presents and comments the final judgment, drawing attention to all elements of legal norm.